EFEKTIVITAS PEMBERIAN DOSIS TINGGI METHYLPREDNISOLONE PADA TRAUMA SPINAL CORD AKUT - Abdul Qodir (LPPMK STIKES Widyagama Husada, 2013)
Acute spinal cord injury is a devastating condition typically affecting young people, mostly males. High-Dose Methylprednisolone treatment in the early hours after the injury is aimed at reducing the extent of permanent paralysis during the rest of the patient’s life. The aim To review randomized trials of High-Dose Methylprednisolone in Acute Spinal Cord Injuries. All randomized controlled trials of steroid treatment for acute spinal cord injury in any language. Data have been extracted from original trial reports. For the NASCIS, Japanese and French trials, additional data (e.g. SDs) have been obtained from the original authors. The evidence produced by this systematic review support the use of high dose methylprednisolone in acute spinal cord injury to improve neurological recovery. Patients who received high-dose methylprednisolone therapy should be observed with intensive in order to reduce complications from such therapy.